Existence of multiple phases and defect states of SnS absorber and its detrimental effect on efficiency of SnS solar cell - Rana, Tanka Raj; Kim, SeongYeon; Kim, JunHo (Current applied physics, 2018)
Tin sulfide (SnS) film is grown by sputtering process with subsequent post-sulfurization. As-deposited SnS consists of orthorhombic and cubic structure SnS whereas post-sulfurized films showed pure orthorhombic crystal structure. This structural transformation was confirmed by X-ray diffraction (XRD), Raman spectroscopy and UV–Vis spectroscopy. We used post-annealed SnS film as an absorber layer of solar cell. The fabricated SnS solar cell was composed of SLG/Mo/SnS/CdS/i-ZnO/ITO. We measured current density-voltage (J-V) and external quantum efficiency (EQE) curves for the completed devices. The best efficiency of SnS solar cell was ∼0.5%. The EQE curve showed existence of multiple phases of SnS, even though XRD and Raman spectroscopy showed pure SnS phase. The multiple phases were observed again by photoluminescence (PL). PL also revealed deep defect states of SnS absorber. Thus, the inhomogeneous SnS absorber is one of the main bottlenecks for high efficiency SnS solar cell. •Tin monosulfide of mixed orthorhombic and cubic structure is grown by sputtering process.•Post-sulfurized SnS was found to be orthorhombic structure by XRD and Raman Spectroscopy.•SnS solar cell demonstrated 0.5% power conversion efficiency.•EQE and PL measurement revealed multiple phases of SnS.•Limiting factors for solar efficiency were multiple phases and defect levels of the absorber.